Pengaruh Pemberian Pupuk Kotoran Sapi Dan Kambing Dengan Dosis Berbeda Terhadap Kualitas Rumput Setaria (Setaria Sphacelata) - Ni Kadek Ayu Wulandari; I Nyoman Kaca; Ni Ketut Etty Suwitari (Fakultas Pertanian, Universitas Warmadewa, 2021)
Forage is the main source of feed for ruminants, both for basic living, growth, production and reproduction. The provision and quality of forage will determine the productivity and development of ruminants. To achieve this, several quality and high production forages have been developed, one of which is Setaria Grass. The way to improve grass product and quality is fertilization using organic fertilizers. Research has been carried out with the aim of knowing the quality of Setaria grass (Setaria sphacelata) fed with cow manure and goat manure with different doses. This study used a 4 Ã— 2 factorial randomized block design (RAK), where 2 types of fertilizer treatments (Factor A) and 4 fertilizer dosage treatments (Factor B) consisted of 8 treatments, namely: D0S without the addition of cow fertilizer), D1S (addition Cow Fertilizer 10 tons / Ha), D2S (Addition of Cow Fertilizer 20 tons / Ha), D3S (Increase Cow Fertilizer 30 tons / Ha), D0K (Without Addition of Goat Fertilizer), D1K (Addition of Goat Fertilizer 10 tons / Ha), D2K (Addition of Goat Fertilizer 20 tons / Ha), and D3K (Addition of Goat Fertilizer 30 tons / Ha). Each treatment was repeated 3 times. The results showed that the type of fertilizer (Factor A) had a significant effect (P <0.05) on the levels of ash, crude protein, crude fiber and fat. Fertilizer dosage (factor B) significantly (P> 0.05) the content of crude protein, crude fiber and crude fat. There was an interaction between the type of fertilizer and the fertilizer dose on the ash content, and crude fiber of Setaria sphacelata grass